Blood Transfusion Information System Design for Blood Transfusion Services Unit - Yulius Harjoseputro (IJITEE (International Journal of Information Technology and Electrical Engineering), 2019)
Information Systems Development as an information provider, both for the users and outsiders, becomes very important at this time. Through a good data management, it can minimize the need for human labor that is currently being replaced by computers. This paper will discuss a design for a blood transfusion information system because there are several issues found in the Blood Transfusion Service Unit (UPTD), some of which are donor data recording at the Blood Transfusion Service Unit which still use manual recording with a book, donors data stored in the book is not well organized, and there are blood donors who do not obey the blood donor regulation, reminder for blood donor level is 70 days and the screening result. This design can do managements which are needed when people want to donor their blood. The database in this system was designed using S-Designor, while the model design was designed using Rational Rose.